Viral Profile of Culex Species Collected from Parts of Accra and Navrongo - Yartey, K.N.Y. (University of Ghana, 2025)
Background: Culex mosquitoes are prevalent in Ghana and play an under-recognised role in arbovirus transmission. However, a proper characterisation of the specific viral profiles carried by these mosquitoes in Ghana is lacking. Rapid urbanisation in Ghana, particularly in Accra, coupled with contrasting ecological conditions in peri-urban Navrongo, creates favourable environments for Culex proliferation and potential arbovirus circulation. This study profiled viral pathogens and broader virome diversity in Culex populations from these two ecologically distinct settings. Methods: A total of 2,886 Culex mosquitoes were collected from parts of Accra and Navrongo and organised into 217 pools for analysis. Conventional PCR assays targeting pan-flaviviruses and pan-alphaviruses were performed on all 217 pools, followed by metagenomic next-generation sequencing (mNGS) on 20 pools. Ten (10) out of the 20 pools yielded reads for downstream analysis. Host-deleted reads were taxonomically classified using Kraken 2, assembled with SPAdes, and viral contigs were annotated with BLASTn. Phylogenetic analysis of major viral families was conducted using maximum likelihood methods. Results: Pan-flavivirus and pan-alphavirus PCR assays yielded no detectable amplification in all Culex pools, suggesting the absence of active infections with classical human-pathogenic arboviruses. Conversely, mNGS revealed a diverse virome comprising 18 viral families. Phylogenetic analysis showed that Ghanaian avian leukosis and myelocytomatosis virus sequences clustered tightly with Indian, Chinese, and American strains, indicating possible historical or ongoing cross-continental viral exchange. Conclusion: This study provides a virome profile of Culex mosquitoes in Ghana, revealing viral diversity despite the absence of major human-pathogenic arboviruses. The findings underscore the ecological complexity of Culex viromes, highlight potential transboundary viral introductions, and demonstrate the value of mNGS for arbovirus surveillance.
MPhil. Medical Microbiology
Keywords: Culex mosquitoes; Ghana; arbovirus transmission